Are We There Yet? A Study of Decentralized Identity Applications - Daria Schumm; Katharina O. E. Muller; Burkhard Stiller (IEEE Access, 2025)
The development of Decentralized Identities (DI) and Self-Sovereign Identities (SSI) aim to address the critical limitations of centralized identity management by enhancing user data control. This has been accompanied by numerous contributions to the development of principles, standards, and systems. While prior surveys have focused primarily on academic literature, they often neglect industry-led efforts and gray literature. Furthermore, no existing survey has thoroughly analyzed real-world deployments to understand the barriers to the adoption of DI and SSI systems. This paper addresses the gap by providing an overview of both academic and gray literature, examining industry-led and governmental initiatives, and presenting a comprehensive landscape of DI and SSI systems. Additionally, the survey identifies the practical challenges and limitations that slow down the transition from centralized to decentralized identity management systems. By shifting the focus from purely technological constraints to real-world deployment challenges, this paper identifies the underlying reasons preventing the adoption of decentralized identities despite their evident benefits to the data owner.